If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4) = 7(x + 2) Reorder the terms: 6(-4 + x) = 7(x + 2) (-4 * 6 + x * 6) = 7(x + 2) (-24 + 6x) = 7(x + 2) Reorder the terms: -24 + 6x = 7(2 + x) -24 + 6x = (2 * 7 + x * 7) -24 + 6x = (14 + 7x) Solving -24 + 6x = 14 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -24 + 6x + -7x = 14 + 7x + -7x Combine like terms: 6x + -7x = -1x -24 + -1x = 14 + 7x + -7x Combine like terms: 7x + -7x = 0 -24 + -1x = 14 + 0 -24 + -1x = 14 Add '24' to each side of the equation. -24 + 24 + -1x = 14 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 14 + 24 -1x = 14 + 24 Combine like terms: 14 + 24 = 38 -1x = 38 Divide each side by '-1'. x = -38 Simplifying x = -38
| 2(x+19)=13x+2(x^2-19) | | 9y^2-6y+5=0 | | 0.4+0.8(4)=0.5(y+4) | | y-15=3.50(x-0) | | 7h-16=47 | | (x-3)-(2x-7)+6=13(x-1)+4(2x+1)-7x | | 2(5x-4)-5(x-3)=2x-2(4-2x) | | 6x-4(-x+10)=x+41 | | 2(3x+4)=4(x-6) | | X=-3y+16 | | 3(x+6)+x=2(x+9)+2 | | -4.3-0.1(g)=-6.1 | | 10*0-6y=-60 | | 2ln(x+9)+3ln(5x+6)= | | 90-x=12+2(90-x) | | y=x+3-x+4+x | | 5-4x-7=2x | | 8p+5r= | | 180-x=-12+2(90-x) | | .99x+100=1 | | 90-x=-12+2(90-x) | | 2.4t-2.1t-2.3=7.6 | | 12=x^3 | | 2b-5=23 | | 33=-8r+9 | | 2y=-4x-4 | | 5x-6=6x-4x | | 6t-1=4t+16 | | 8x-115=2x-5 | | 6+65x=39x+24 | | 12x^3+2x^2-18x-3=0 | | 7x-3(4x-1)=0 |